Changes in GABA and glutamate concentrations during memory tasks in patients with Parkinson’s disease undergoing DBS surgery - Buchanan, Robert J.; Darrow, David P.; Meier, Kevin T.; Robinson, Jennifer; Schiehser, Dawn; Glahn, David; Nadasdy, Zoltan (Frontiers in Human Neuroscience, 2014)
Until now direct neurochemical measurements during memory tasks have not been accomplished in the human basal ganglia. It has been proposed, based on both functional imaging studies and psychometric testing in normal subjects and in patients with Parkinson’s disease (PD), that the basal ganglia is responsible for the performance of feedback-contingent implicit memory tasks. To measure neurotransmitters, we used in-vivo microdialysis during deep brain stimulator (DBS) surgery. We show in the right subthalamic nucleus (STN) of patients with PD a task-dependent change in the concentrations of glutamate and GABA during an implicit memory task relative to baseline, while no difference was found between declarative memory tasks. The five patients studied had a significant decrease in the percent concentration of GABA and glutamate during the performance of the Weather Prediction Task (WPT). We hypothesize, based on current models of basal ganglia function, that this decrease in the concentration is consistent with expected dysfunction in basal ganglia networks in patients with Parkinson’s disease.